ПОВЫШЕНИЕ ЭФФЕКТИВНОСТИ ПОЛУЧЕНИЯ УЛЬТРАДИСПЕРСНЫХ ЧАСТИЦ МЕТАЛЛОВ ОБЪЕМНЫМ ЭЛЕКТРОЭРОЗИОННЫМ ДИСПЕРГИРОВАНИЕМ ИХ ГРАНУЛ В ЖИДКОСТИ - Захарченко, С.Н. (Інститут електродинаміки НАН України, Київ, 2012)
The basic processes of transformation of energy of electric pulses generators in other kinds at volume electroerosive dispersion of metal granules in a liquid have been considered. Practical recommendations about decrease of losses of energy at obtaining of submicronic electroerosive particles by the given method are given. It is shown that limitation of energy of plasma channels raises probability of restriction of their evolution by a stage of a streamer and promotes decrease in the sizes of electroerosive particles.The comparative analysis of features of electroerosive dispersion of layers of metal granules by gas-dynamic, hydrodynamic and vibrating activations them. It is shown that vibrating activation makes possible to start working simultaneously three independent channels of restriction of energy of an electric pulse: on pressure, on a current and on duration. It promotes decrease of a percentage of spark channels in favor of streamers and, as consequence - to reduction of the sizes of erosive particles to 1 micron and less. References 13.